Fibroblast Growth Factor 10 Attenuates Renal Damage by Regulating Endoplasmic Reticulum Stress After Ischemia–Reperfusion Injury - Tan, Xiaohua; Yu, Lixia; Yang, Ruo; Tao, Qianyu; Xiang, Lijun; Xiao, Jian; Zhang, Jin-San (Frontiers in Pharmacology, 2020)
Renal Ischemic reperfusion (I/R) injury is a predominant cause of acute kidney injury (AKI), the pathologic mechanism of which is highly complex involving ROS (Reactive Oxygen Species) accumulation, inflammatory response, autophagy, apoptosis as well as endoplasmic reticulum (ER) stress. Fibroblast growth factor 10 (FGF10), as a multifunctional growth factor, plays crucial roles in embryonic development, adult homeostasis, and regenerative medicine. Herein, we investigated the molecular pathways underlying the protective effect of FGF10 on renal I/R injury using Sprague-Dawley rats. Results showed that administration of FGF10 not only effectively inhibited I/R-induced activation of Caspase-3 and expression of Bax, but also alleviated I/R evoked expression of ER Stress-related proteins in the kidney including CHOP, GRP78, XBP-1 and ATF-4 and ATF-6. The protective effect of FGF10 against apoptosis and ER Stress was recapitulated by in vitro experiments, using oxidative damaged NRK-52E cells induced by tert-Butyl hydroperoxide (TBHP). Significantly, U0126, a selective non-competitive inhibitor of MAP kinase kinases (MKK), largely abolished the protection role of FGF10. Taken together, both in vivo and in vitro experiments indicated that FGF10 attenuates I/R-induced renal epithelial apoptosis by suppressing excessive ER stress, which is, at least partially, mediated by activation of the MEK-ERK1/2 signaling pathway. Therefore, our present study revealed the therapeutic potential of FGF10 on renal I/R injury.